Investigation of the Sturm–Liouville problems with integral boundary condition - Skučaitė, Agnė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2011)
This paper presents some new results on the spectrum of a complex plane for the second order Finite-Difference Scheme with one integral type nonlocal boundary condition (NBC). We analyze how complex eigenvalues of these problems depend on the parameters of the integral NBC. The integral conditions are approximated by the trapezoidal rule or by Simpson’s rule.
Keywords: Finite-Difference Scheme; Nonlocal Boundary Condition; complex eigenvalues